2005
DOI: 10.1093/jnci/dji428
|View full text |Cite
|
Sign up to set email alerts
|

Clonal History of Papillomavirus-Induced Dysplasia in the Female Lower Genital Tract

Abstract: These data indicate that high-grade dysplastic lesions in the female lower genital tract may emerge primarily as monoclonal lesions from a transformed cell population derived from the uterine cervix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
63
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 31 publications
3
63
1
4
Order By: Relevance
“…A significantly higher number of cases with a single HR type had severe dyskaryosis compared with other cytology grades and no such correlation with disease progression was found in cases with multiple HR types. Others have recognised the clonal expansion of a single integrated HR type and subsequent cervical neoplasia development (Vinokurova et al, 2005) and our data would support this observation and suggests that there is little, if no, synergy between multiple HPV types in terms of neoplastic effect (Fife et al, 2001). However, the overall HPV type-specific distribution in cases with multiple HR types is not a direct reflection of that observed in cases with a single HR type, and of interest was the equivalent representation of HPV 16 (Figure 1).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A significantly higher number of cases with a single HR type had severe dyskaryosis compared with other cytology grades and no such correlation with disease progression was found in cases with multiple HR types. Others have recognised the clonal expansion of a single integrated HR type and subsequent cervical neoplasia development (Vinokurova et al, 2005) and our data would support this observation and suggests that there is little, if no, synergy between multiple HPV types in terms of neoplastic effect (Fife et al, 2001). However, the overall HPV type-specific distribution in cases with multiple HR types is not a direct reflection of that observed in cases with a single HR type, and of interest was the equivalent representation of HPV 16 (Figure 1).…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, clonal expansion of a single integrated HR type and cervical neoplasia development has been reported (Vinokurova et al, 2005). Social deprivation has been associated with cervical cancer incidence, but other co-factors such as age, smoking, education and reduced participation in screening also require consideration (de Sanjosé et al, 1997;Krieger et al, 1999;Parikh et al, 2003).…”
mentioning
confidence: 99%
“…1,[4][5][6][7] Previous studies regarding HPV types in VAIN and vaginal cancer or comparisons of HPV types between incident vaginal and previous cervical lesions were limited by small sample sizes and inconsistent conclusions. 3,4,[8][9][10][11][12][13][14][15] Smith et al 8 published a systemic review of 725 abstracts, in which the HPV detection rates among 166 cases of VAIN2/3 and 66 cases of VAIN1 were 92.6% and 98.5%, respectively. Another systemic review of 22 U.S. studies found HPV16/18 to be the predominant type in VAIN3 (n ¼ 97, 65.1%).…”
mentioning
confidence: 99%
“…2 Fortunately most women are able to clear the infection, and less than 10% of infected women develop a persistent HPV infection which causes dysplasia of the lower genital tract and might cause VIN. 3 Such a persistent infection with high-risk HPV (mostly HPV16, 18, 31 or 33) may trigger VIN to further develop into invasive vulvar cancer. What percentage of women with VIN eventually develop cancer is difficult to assess, because most patients with VIN will be treated effectively.…”
mentioning
confidence: 99%